2018
DOI: 10.29252/jhehp.4.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Assessment Matrix; Results of a Delphi Study

Abstract: Journal homepage: www.zums.ac.ir/jhehp Background: Identification of hazards is one of the most important parts of industries' strategies. This can be done using a hazard matrix as an applicable tool which can also rank hazards properly. Methods: In this study, the Delphi method was used to select best alternatives for a hazard matrix. All possible items were gathered and passed Delphi rounds, in which mean, median and standard deviation were used to evaluate decisions. Moreover, Kendall's coefficient of conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…SSCPs are associated with S&H risks [13,28], and the results of ANN modeling in the present study indicated that some RMFs could also predict AFR, including HAZID, periodic risk assessment, development and implementation of risk control measures, and housekeeping. Moreover, some researchers have reported that the most important influential factors in SSCP accidents are the weaknesses of the S&H risk management systems, such as the deficiencies in HAZID, risk assessment, and risk control [22,29,30]. Some of the limitations of this analytical study were the small number of the considered accidents-related factors in the model and geographical sprawl of the SSCPs.…”
Section: Feature Selectionmentioning
confidence: 99%
“…SSCPs are associated with S&H risks [13,28], and the results of ANN modeling in the present study indicated that some RMFs could also predict AFR, including HAZID, periodic risk assessment, development and implementation of risk control measures, and housekeeping. Moreover, some researchers have reported that the most important influential factors in SSCP accidents are the weaknesses of the S&H risk management systems, such as the deficiencies in HAZID, risk assessment, and risk control [22,29,30]. Some of the limitations of this analytical study were the small number of the considered accidents-related factors in the model and geographical sprawl of the SSCPs.…”
Section: Feature Selectionmentioning
confidence: 99%
“…Not only are health care workers at various risks, but there are also environmental problems in these centers that endanger public health (5). Additionally, given that Iran is exposed to a variety of natural and man-made hazards, and according to the Global Assessment Report on Disaster Risk Reduction, Iran's risk level only for natural hazards taking into account about 106,000 deaths over the past four decades, is estimated to be 8 out of 10 (6).…”
Section: Introductionmentioning
confidence: 99%